Inflammatory Bowel Disease - Kaser, Arthur (Annu Rev Immunol, 2010)
Insights into inflammatory bowel disease (IBD) are advancing rapidly owing to immunologic investigations of a plethora of animal models of intestinal inflammation, ground-breaking advances in the interrogation of diseases that are inherited as complex genetic traits, and the development of culture-independent methods to define the composition of the intestinal microbiota. These advances are bringing a deeper understanding to the genetically determined interplay between the commensal microbiota, intestinal epithelial cells, and the immune system and the manner in which this interplay might be modified by relevant environmental factors in the pathogenesis of IBD. This review examines these interactions and, where possible, potential lessons from IBD-directed, biologic therapies that may allow for elucidation of pathways that are central to disease pathogenesis in humans.